Consumer research: introspective essays on the study of consumption - Holbrook, Morris B. (California: Sage, 1995)
Los temas principales son: A Brief history of morris the cat, theory development is a jazz solo, on hatching a program of consumer research, what is consumer researcch, o, consumer, how you?ve changed, whither consumer research, romanticism, subjective personal introspection, and morris the epicurean, the role of lyricism in consumer research
Keywords: Marketing; Mercado del Consumidor